Interstices Issue 19: Presence CFP - Gatley, Julia; Barrie, Andrew; Douglas, Andrew; Jenner, Ross; Hedges, Susan (Interstices: Journal of Architecture and Related Arts)
Interstices Journal of Architecture and Related Arts Issue 19: PRESENCE Submission deadline 12th October Buildings, cities, landscapes, sculptures, paintings, and music, even, are already physically present and persisting in a present. Why theorise their presence, and what relevance could such a notion have for arts rooted in space? The contemporary emphasis on the physical, material, performative and atmospheric – rather than on meaning – is a reaction against the overly discursive and semiotic strains of ‘80s post-modernism, when the identification and attribution of meaning became a core practice of architectural thought. Afterwards, materiality and its effects assumed what Hans Ulrich Gumbrecht terms a “non-hermeneutic” presence (2004: 1-20), coinciding with the much vaunted ‘post-theory’ in architecture and its rejection of criticality. Today, we no longer believe that theory has been surpassed, nor, by the same token, that a complex of meanings can be kept separate from its mediality, that is, from material. Neither is pure manipulation of data, without aesthetic and bodily intention, able to produce architecture. The material and the immaterial are not easily divided. While presence concerns communication, it concerns space even more—through its occupation (or dis-occupation) and activation. Gumbrecht reminds us that, what is ‘present’ to us (in the sense of the Latin prae-esse), is “in front of us, in reach of and tangible for our bodies” (17). He reminds us also of George Steiner’s remarks that the arts, “wonderfully rooted in substance, in the human body, in stone, in pigment, in the twanging of gut or the weight of wind on reeds”, begin, but do not end, in immanence. The task of the aesthetic is to “quicken into presence the continuum between temporality and eternity, between matter and spirit, between man and ‘the other’” (Steiner, 1989: 227). Absence of presence is not the same as presence of absence, in which traces, silences or voids powerfully embody (and make present) something not present. For example, the voids of Berlin: Daniel Libeskind, Peter Eisenman; or the voids of Eduardo Chillida, Jorge Oteiza and Tadao Ando; the silence of John Cage and the mā of Toru Takemitsu—they all involve experience and affect. By contrast, representation seems to be involved with the “age of the sign” and “conceptual deduction” (Gumbrecht, 2004: 57). However, as Jean-Luc Nancy points out in France, representation “is as old as the West”, and maybe there is “no humanity (and, perhaps, no animality) that does not include representation” (1993: 1). Nancy’s conception of presence does not refer to a permanent state, but to nascence: “Presence itself is birth, the coming that effaces itself and brings itself back” (5). Gumbrecht relates this wavering to the double movement of withdrawal and unconcealment in Martin Heidegger, particularly in relation to his account of a Greek temple in terms of presence via the notions of “earth” and “world”. Here, “the sheer presence of the temple triggers the unconcealment of a number of things—in their thingness—that surround the temple” (Gumbrecht, 2004: 73). For Nancy the very act and pleasure of drawing, insofar as it is “the opening of form” (2013: 1), is also a nascence. What would it mean for a drawing, building, artwork or poem to perform or keep alive the performance of its birth? Perhaps the malleability of Alvaro Siza’s works (Molteni 2003) or Lemi Ponifasio’s irruptive choreography (Ponifasio, 2009) provide some hints to the potential of works’ in statu nascendi. In addition, a human tendency to endow buildings and artworks with life includes practices involving the holy and tapu, such as sacrifice, rites of foundation and the address to a living ancestor (in whare and fale, for example). These frame, stage and enact the effect of “living presence” – exceeding an aesthetic stance of disinterested contemplation of art’s formal qualities (Eck, 2015: 172). “Studying what makes viewers deny the representational character of art”, argues van Eck, “will help understanding why art is such a universal feature of human life” (209). After all, “aesthetic experience” provides feelings of intensity unknown in specific everyday worlds; there is no aesthetic experience without presence effects emerging seemingly out of nowhere. In all fields of art practice, what might be the status of presence in Virtual Reality and digital representation obsessed with verisimilitude? How can even purposeful design, particularly in an era of parametricism, retain an element of the status nascendi, as unprogrammed (or even unprogrammable) emergence? The “joy of averring oneself to be continually in the state of being born—a rejoicing of birth, a birth of rejoicing” (Nancy, 1993: back cover) requires an acceptance, even embrace, of the fact that existence “comes nude into the world”. It is with this sense of Presence that we invite you to submit a paper for the forthcoming issue of Interstices. For various publishing options and the required formatting, please refer to the Guidelines for Submissions on the Interstices website. Call for Papers Interstices: Journal of Architecture and Related Arts invites submissions for issue 21 of the journal due for publication in March 2019. Authors may submit academic and practice-oriented, fully written as well as visual, contributions for this issue. Please submit full papers for the Interstices 21 journal issue to Sue Hedges (susan.hedges@aut.ac.nz) by 12th October 2018. Submissions may comprise up to 5000 - 7000 word papers or visual/audio/moving image works with an accompanied text of approximately 500 words. All submission will be double blind refereed. The journal’s non-refereed section welcomes papers up to 2500 words, as well as project reports and reviews of up to 1000 words. Visit our website to view the Guidelines for Submissions for details about the reviewing process, copyright issues and formatting: http://www.interstices.ac.nz/information-for-contributors/guidelines-for-submissions/ We look forward to your contribution! Journal editors: Andrew Barrie, Andrew Douglas, Julia Gatley, Susan Hedges, Ross Jenner, References Eck, C. (2015). Art, agency and living presence: From the animated image to the excessive object. Boston, MA: De Gruyter. Gumbrecht, H. U. (2004). Production of presence: What meaning cannot convey. Stanford, CA: Stanford University Press. Nancy, J-. L. (1993). The birth to presence (B. Holmes Et Al. Trans.). Stanford, CA: Stanford University Press. Nancy, J. L. (2013). The pleasure in drawing (P. Armstrong, Trans.). Oxford, UK: Oxford University Press. Ponifasio, L. (2009) Tempest : Without a body [performance] Retrieved from https://www.youtube.com/watch?v=WfLqv85uCww&feature=player_embedded Molteni, E. (2008). “Comme un sculpteur, on doit maintenir l’argile humide”. Casabella, 763, 11. Steiner, G. (1989). Real presences: Is there anything in what we say?. London, UK: Faber.